The Existence of Islamic Law in Indonesia and Its Implementation in the Crime of Adultery - Mujahid Imaduddin (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2026)
Islamic law constitutes an essential element in the development of Indonesia's national legal system as an empirically living law in society. National law is grounded in Pancasila values that uphold religious and just and civilized human values. Nevertheless, many legal products remain contrary to these Pancasila values, including adultery offenses, which continue to reflect individualistic and liberal colonial heritage. This research examines: (1) the existence and position of Islamic law in Indonesia's national legal system; (2) theories of Islamic law reception and their methodological limitations; and (3) the implementation of Islamic law in the reformulation of adultery offenses within the National Criminal Code (KUHP) based on the principles of purification and integration. This study employs normative legal research methodology utilizing philosophical, statutory, and conceptual approaches. Primary legal materials include the Qur'an, Sunnah, the 1945 Constitution, the Wetboek van Strafrecht (WvS), and the National Criminal Code (Law No. 1 of 2023). The findings conclude that Islamic law has long existed and is deeply rooted in Indonesia's legal system since the 7th century CE. The implementation of Islamic law in national legal development must proceed through two interrelated processes: purification and integration. The concrete manifestation is the reformulation of adultery offenses in the National Criminal Code to better align with Maqāṣid al-Sharī'ah principles and Pancasila values.